On modification of eutectic cast iron graphite - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия)
It has been shown that elementary crystalline cells of graphite and basic products of iron modification do not correspond to the principle of structural and dimensional correspondence of Dankov –Konobeevsky. Modifying elements Al, Ca, Mg, Ba, Ce increase the phase tension melt‑graphite by binding surface‑active oxygen and sulfur. Modifying cast iron eutectic graphite is a nanostructured process in which modifying elements refine elemental graphite nanocrystals from adsorbed oxygen and sulfur atoms. This contributes to an increase in the concentration of graphite nuclei upon solidification of the cast iron melt. The modification reduces the concentration of dissolved hydrogen, which increases the effectiveness of the modifying effect. Reduced concentrations of demodifying surface‑active elements, melt degassing, increased heat removal contribute to increasing the degree of branching and compactness of graphite dendrites during iron crystallization. The strongest modifying element of eutectic cast iron graphite is magnesium.